Предмет: Математика,
автор: genryls
(2x-1)(3x+2)=6(x^2-x+2)
2-(3x-7)=-2(x+1)
(5y-1)(5y-+1)=25y^2-(3y-2)
решите пожалуйста
Ответы
Автор ответа:
0
Ответ:
1. 2
2. 11
Пошаговое объяснение:
1) (2x-1)(3x+2)=6(x^2-x+2)
6x^2+4x-3x-2=6x^2-6x+12
6x^2-6x^2+4x-3x+6x=12+2
7x=14
x=2
2) 2-(3x-7)=-2(x+1)
2-3x+7=-2x-2
2x-3x=-2-9
-x=-11
x=11
3) это если там минус во второй скобке :
(5y-1)(5y-1)=25y^2-(3y-2)
25y^2-5y-5y+1=25y^2-3y+2
25y^2-25y^2-10y+3y=2-1
-7y=1
7y=-1
y=
а это если плюс во второй скобке:
(5y-1)(5y+1)=25y^2-(3y-2)
25y^2+5y-5y-1=25y^2-3y+2
25y^2-25y^2+3y=2+1
3y=3
y=1
Похожие вопросы
Предмет: Математика,
автор: kasatonova4880
Предмет: Математика,
автор: hurka861
Предмет: Математика,
автор: DefEnser5256
Предмет: Литература,
автор: amina240720046
Предмет: История,
автор: азаща1